Persistent Overconfidence and Biased Memory: Evidence from Managers - Huffman, David; Raymond, Collin; Shvets, Julia (American Economic Review, 2022)
A long-standing puzzle is how overconfidence can persist in settings characterized by repeated feedback. This paper studies managers who participate repeatedly in a high-powered tournament incentive system, learning relative performance each time. Using reduced form and structural methods we find that (i) managers make over-confident predictions about future performance; (ii) managers have overly positive memories of past performance; (iii) the two phenomena are linked at an individual level. Our results are consistent with models of motivated beliefs in which individuals are motivated to distort memories of feedback and preserve unrealistic expectations. (JEL D82, D83, J33, L25, L81, M52, M54)